2003
DOI: 10.1002/jmv.10401
|View full text |Cite
|
Sign up to set email alerts
|

Performance of two commercially available sequence‐based HIV‐1 genotyping systems for the detection of drug resistance against HIV type 1 group M subtypes

Abstract: The use of genotyping assays for the detection and evaluation of drug resistance mutations within the polymerase gene of human immunodeficiency virus type 1 (HIV-1) is becoming increasingly relevant in the clinical management of HIV-1 infection. However, genotypic resistance assays available currently have been optimised for genetic subtype B strains of the virus and many clinical centres are presented with strains from subtypes A, C, and D. In the present report, we compare the performance of two sequence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 9 publications
4
19
0
Order By: Relevance
“…To date, the HIV subtype distribution in Poland was similar to that reported for Western 182 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 shown to be highly efficient for B clade sequencing, their detection thresholds for non-B variants is 240 lower [Beddows 2003]. Therefore, the possibility that some variants may have gone undetected 241 exists, however, only these detection methods were available.…”
supporting
confidence: 85%
“…To date, the HIV subtype distribution in Poland was similar to that reported for Western 182 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 shown to be highly efficient for B clade sequencing, their detection thresholds for non-B variants is 240 lower [Beddows 2003]. Therefore, the possibility that some variants may have gone undetected 241 exists, however, only these detection methods were available.…”
supporting
confidence: 85%
“…Our finding that version 1.5 of the TruGene assay enables non-B HIV-1 subtype viruses to be sequenced with a high success rate is consistent with previous studies examining the performance characteristics of this version of the assay (5,15,20). The primary difference between versions 1.0 and 1.5 of the TruGene HIV-1 genotyping assay is a modification to the RT-PCR primers (20).…”
Section: Discussionsupporting
confidence: 87%
“…The two commercially available genotyping assays, the Viroseq HIV-1 genotyping system (Celera, Alameda CA) and the TruGene HIV-1 genotyping system (Siemans Medical Solutions Diagnostics, Tarrytown, NY), were designed and approved by the FDA for HIV-1 subtype B only. Although studies have indicated that these assays can be used for other HIV-1 group M subtypes, the reported sensitivities vary (2,10,11,29,33). The assay we report here and the one reported recently by Buckton et al (7) are the only assays that have directly addressed subtype-genotyping-efficiency issues.…”
Section: Discussionmentioning
confidence: 68%